Щодо розповсюдження деяких типів металевих (мідно-бронзових) прикрас в складі поховань ранньої та середньої бронзи степових культур України - Черних, Л.А. (Археологія і давня історія України, 2021)
У статті розглядаються деякі підсумки вивчення окремих типів кованих прикрас, відомих за
матеріалами ямної та катакомбних культур —
характер їхнього поширення в територіальному
і хронологічному діапазонах на теренах України,
їхні морфологічні модифікації. Based on the materials of the Yamnaya and the
Catacomb CHC (culture-historical community), the
types of forged ornaments of the burial garment, made
on the basis of thin copper / bronze plates-beads and
hoops, their morphological modifications, position on
the garment, spreading in territorial and chronological
aspects are analyzed. The quantitative characteristics
are given against the background of a representative
sample of burials from the main areas of the indicated
cultures of Ukraine (tables 1—3). The irregular
spreading of these types of jewelry was established,
which is explained both by the technical capabilities
of production and the specificity of local ethno-cultural
traditions.
The massifs of the North-Western Black Sea region
are distinguished by the quantitative predominance of
spikes and small hoops, which emphasizes the special
cultural context of the Budjak Culture of the Early
Bronze Age in the region. The prevailing trend of their
use in the composition of typesetting bracelets is also
noted here. These types of jewelry are much less represented
in other regions of the Yamnaya CHC, where
the prevailing trend is their use in necklaces, hats or
hairstyles, and the use of hoops in the decoration of a
waist belt.
The appearance in burials of the EBA / MBA of rare
finds of spiral beads, small items with punch ornaments,
hoops-bracelets reflects the desire for a variety
of «lamellar» decorations in the context of traditional
technologies. Large hoops with punch ornaments are a
special type. Being a continuation in the development of
symbolic objects of steppe cultures of the Ponto-Ciscaucasian
community, they are an innovation of the Early
Catacomb tribes of the Northern Black Sea region.
The Middle Bronze Age is the time of the appearance
of numerous types of cast ornaments, which to a
certain extent replace forged ones, which took place
mainly in Donets river region with sources of raw
materials and close to the advanced technologies foci.
Beads are found sporadically in the catacomb burials of
Donets river region (Donetsk and Late Catacomb burials)
and small hoops are absent. The Ingul Catacomb
Culture is distinguished by the presence of small plate
ornaments, which reflects the persistent archaism of
local metalworking.